The Effect of Diabetes Self Management Education (DSME) with Audiovisual Media on Self-Care and Decreasing Blood Sugar Levels in Diabetes Mellitus Patients Type II - Nugrahenny, Fabella Finandatyan; Darmawan, Rendi Editya; Lestari, Siti (Future Science, 2022)
Background: Diabetes mellitus (DM) is a metabolic disease characterized by hyperglycemia that occurs due to abnormal insulin secretion. Diabetes Self Management Education (DSME) is an important role in preventing or delaying complications in people with pre-diabetes and diabetes. Aim of study is to analize effect of Diabetes Self Management Education (DSME) with audiovisual media on self-care and decreasing blood sugar levels in diabetes mellitus patients type II Methods: Using a quasy experiment research design with control group design. Samples is 34 respondents (17 respondents in the control group and 17 respondents in the experimental group) that chosen randomly with odd and even way according to data patients DM. Self care measured by Summary of Diabetes Self-Care Activity (SDSCA) questionnaire, and blood sugar level measure with a glucometer. Intervention group given DSME for 14 days, and control group get treatment according to community standards. Bivariate analysis used the non-parametric Wilcoxon test and to see the difference between pre-test and post-test on the self-care variable and to see the differences between groups using the Mann-Whitney test. Analysis of bivariate test on blood sugar levels drop variables using parametric test Paired T-Test and to see the difference between groups using Independent T-Test test. Results: The results of the Wilcoxon test of self-care control group p=0.246 (p=<0.05), so there is no effect, the experimental group p = 0.005 (p=<0.05), so that concluded no effect. Mann-Whitney test results with personal care and experimental control group p=0.000 (p=<0.05), so that there is a significant difference. Results of Paired T-Test blood sugar control group p = 0.812 (p =<0.05), so there is no effect, the experimental group, p = 0.000 (p=<0.05), so that concluded no effect. The results of the Independent T-Test blood sugar levels in the control and experimental groups p=0.020 (p=<0.05), so there is a significant difference in effect. Conclusion: There is the influence of Diabetes Self-Management Education (DSME) The Audiovisual Media on self-care and decrease blood sugar levels in people with Type II DiabetsMellitus.